Odniesienia międzyjęzykowe w świetle nazw miejscowych pogranicza polsko-ruskiego - Wysoczański, Włodzimierz (Acta Polono-Ruthenica, 2006)
This article shows interlingual references in the context of toponyms of borderlands. Synthesizing approach reflects specificity of Polish-Ruthenian borderland concerning onymic categories of linguistic and cultural sign in the borderland, specific features of toponyms in Polish-Eastern- Slavonic borderland, and the analysis of the oikonymy in Polish-Ruthenian borderland. The latter cognitive complex basically includes following matters: research on the toponyms of Polish- Ruthenian borderland, the way their formation was influenced by the contacts of various ethnolects, the conditioning of toponymy in Polish-Eastern-Slavonic borderland, the localisation of toponyms, transitional oikonymic system, coexistence of official and unofficial names, translation of toponyms.